2014
DOI: 10.1149/2.0011502jes
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ether-Based Ionic Liquid Electrolytes for Lithium-O2Batteries

Abstract: In this work, we showed the results of the characterization of ether based electrolytes for Li-O 2 batteries, prepared by mixing TEGDME and N-methoxyethyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)-imide ionic liquid (IL). The mixtures having different ratio TEGDME/IL and containing LiCF 3 SO 3 salt, were thoroughly characterized by thermal analysis, conductivity and electrochemical stability measurements. Their potential use as electrolytes in Li-O 2 batteries was checked investigating Li/TEGDME-IL/O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…Ionic liquids (ILs) have attracted considerable interest in recent years for potential application as electrolyte in novel battery systems or as additive in electrolyte mixtures because of a number of interesting properties such as very low vapour pressure, low flammability and high thermal and electrochemical stability, and inherent ionic conductivity. For these applications the electrochemical stability is a key aspect, since the high cell voltages of such systems are likely to exceed the stability range of traditional organic electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) have attracted considerable interest in recent years for potential application as electrolyte in novel battery systems or as additive in electrolyte mixtures because of a number of interesting properties such as very low vapour pressure, low flammability and high thermal and electrochemical stability, and inherent ionic conductivity. For these applications the electrochemical stability is a key aspect, since the high cell voltages of such systems are likely to exceed the stability range of traditional organic electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the performance of ionic liquids could be synergistically improved by blending with aprotic solvents, such as PYR 14 TFSI/TEGDME electrolyte, [120] 1-butyl-1-methyl-pyrrolidinium bis(trifluoromethylsulfonyl)imide ([BMP][NTf 2 ])/ DMSO electrolyte, [127] N-methoxyethyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)-imide (PYR 1,2O1 TFSI)/TEGDME electrolyte, [128] …”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…In addition, the performance of ionic liquids could be synergistically improved by blending with aprotic solvents, such as PYR 14 TFSI/TEGDME electrolyte, 1‐butyl‐1‐methyl‐pyrrolidinium bis(trifluoromethylsulfonyl)imide ([BMP][NTf 2 ])/DMSO electrolyte, N ‐methoxyethyl‐ N ‐methylpyrrolidinium bis(trifluoromethanesulfonyl)‐imide (PYR 1,2O1 TFSI)/TEGDME electrolyte, N‐ butyl‐ N,N ‐dimethyl‐ N ‐ethylammonium bis(trifluoromethyl)sulfonylimide [N 1124 ][TFSI]/TEGDME electrolyte, and PYR 14 TFSI/DME electrolyte . For example, PYR 14 TFSI/TEGDME electrolyte demonstrated enhanced kinetics and reversibility for the oxygen reactions due to the significantly improved conductivity of the TEGDME electrolyte by blending with PYR 14 TFSI ionic liquid, resulting in a lower overpotential during the charge process compared with the solely TEGDME electrolyte .…”
Section: Nonaqueous Electrolytementioning
confidence: 99%
“…However, this reaction suffers from low reversibility leading to a low cyclability of the battery. Recently, Room Temperature Ionic Liquids (RTILs) attracted much attention for Li−O 2 battery electrolyte . Namely, Nakamoto et al .…”
Section: Ionic Conductivity Viscosity Degradation Temperature Capamentioning
confidence: 99%
“…Recently, Room Temperature Ionic Liquids (RTILs) attracted much attention for LiÀO 2 battery electrolyte. [2][3][4][5][6][7][8][9][10][11][12] Namely, Nakamoto et al [13] demonstrated the advantage of the RTILs stability against electrochemical oxidation vs. Li + /Li and O 2 redox reversibility. Cai et al [14] proved that ionic liquid could show higher specific capacity compared to carbonate solvent electrolytes.…”
mentioning
confidence: 99%